The use of authentic spoken materials in english as a foreign language (EFL) classroom - Dian Fajrina (Proceedings of AICS - Social Sciences, 2013)
Learning a second language will be considered succeed when the learner is able to speak in the language s/he is studying (Nunan, 1999). Speaking is not merely about being able to pronounce the word correctly, using the appropriate stress and intonation, but more important is to survive in the different context where the conversation is taking place (Harmer, 1997). This paper offers to use authentic materials in the English as a Foreign Language (EFL) speaking classroom since authentic gives students “exposure to real language and its use in its own community” (Widdowson, 1990).  Authentic materials are materials that we can use in the classroom and that have not been changed in any way for EFL students (Sanderson in Tamo, 2009). The use of authentic materials in EFL speaking classroom will give students chances to encounter the real world and how the language is really used. They are also said to be motivating, giving students sense of achievement when able to communicate as the native speakers do. Therefore, it is recommended that teachers use authentic spoken materials in EFL classroom audio visually to enable students to imitate native speakers of English in speaking, not only on how to pronounce the words correctly and using the appropriate stress in speaking, but also able to use correct body language to avoid cultural misunderstanding. However, both teacher and students also need to be aware of a few disadvantages of using different sources of authentic materials, especially when dealing with culture issues. Teachers are also encouraged to give pedagogical support for students when dealing with listening tasks and literary texts. Key words: Speaking, teaching speaking, authentic materials, EFL classroom